Use Of Stored Srin Grafis In Resurfacing Of Wounds (An experience of 100 cases) - Lt Col J. C. Sharma (Indian Journal of Plastic Surgery, 1981)
Stored split thickness skin grafts were for resurfacing wounds of various types in 100 cases, The grafts were applied in the ward after 24-58 hours delay and were treated by exposure method. The advantages claimed are a better take of the graft, reduced blood loss, and less operation time, economy in dressing and participation of ward staff in the management of these cases.